Solving a quadratic by completing the square

preview_player
Показать описание
👉 Learn how to solve quadratic equations by completing the square. When solving a quadratic equation by completing the square, we first take the constant term to the other side of the equation and create a perfect square trinomial with the quadratic term and the linear term in the right hand side of the equation.

This is done by adding to both side of the equation, the square of half the coefficient of the linear term (the term whose variable is not squared). Then the perfect square trinomial is evaluated and then we solve for the variable to get the solution(s) to the quadratic equation.

Organized Videos:
✅How to Solve a Quadratic by Completing the Square
✅Solve a Quadratic by Completing the Square | Fractions
✅Solve a Quadratic by Completing the Square | -x^2+bx+c
✅Solve a Quadratic by Completing the Square | 2x^2+bx+c
✅Solve a Quadratic by Completing the Square | ax^2+bx+c
✅Solve a Quadratic by Completing the Square | x^2+bx+c
✅Solve a Quadratic by Completing the Square | Learn About

Connect with me:

#Solvequadratics #completethesquare #brianmclogan
Рекомендации по теме
Комментарии
Автор

Explained very nicely. Thank you. PSD.

pritamdhinsa
Автор

There's a way to complete the square without having to deal with fractions. Use the formula, c=(b/2)^2•(1/a) to complete the square.

x^2+3x-6=0
4x^2+12x-24=0
4x^2+12x=24
4x^2+12x+9=24+9
(2x+3)^2=33
|2x+3|=_/33

2x+3=_/33
2x=-3+_/33
x=(-3+_/33)/2 🏳️‍🌈

2x+3=-_/33
2x=-3-_/33
x=(-3-_/33)/2 🏳️‍🌈

ChavoMysterio